1986
DOI: 10.1152/jappl.1986.61.2.734
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory mechanics in men following a deep air dive

Abstract: The mechanical properties of the lungs were measured in 10 men before and after a simulated air dive to 285 ft of seawater (87 m). The objective was to determine whether a dive likely to produce pulmonary bubble emboli would alter lung mechanics. Lung function was measured predive and at 1, 2, 3, 6, 7, and 23 h postdive. Measurements of lung function were also made at identical times on a control day when no dive was made. Each set of measurements included precordial Doppler signals, pulmonary resistance, quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Several studies showed that dry chamber dives using air as a breathing gas did not reveal significant changes in expiratory flows or volumes up to 24 h after simulated depths of 39-87 m [16][17][18][19]. However, a temporary decrease in the diffusion capacity of the lung for carbon monoxide (DLCO) was shown [17], reaching a maximum at 20 min post-dive, which was significantly correlated with venous gas microbubbles detected using Doppler ultrasound.…”
Section: Short-term Effects Of Diving On Lung Functionmentioning
confidence: 99%
“…Several studies showed that dry chamber dives using air as a breathing gas did not reveal significant changes in expiratory flows or volumes up to 24 h after simulated depths of 39-87 m [16][17][18][19]. However, a temporary decrease in the diffusion capacity of the lung for carbon monoxide (DLCO) was shown [17], reaching a maximum at 20 min post-dive, which was significantly correlated with venous gas microbubbles detected using Doppler ultrasound.…”
Section: Short-term Effects Of Diving On Lung Functionmentioning
confidence: 99%
“…A post-dive decrease of pulmonary diusing capacity has been found to be associated with pulmonary microembolization by nitrogen bubbles that have been liberated from supersaturated tissues after decompression from a hyperbaric air atmosphere (Dujic et al 1993; Thorsen et al 1995). Evidence of changes in lung volumes and¯ow rates after a single scuba dive is contradictory: a variety of studies on lung function in divers after simulated dry chamber dives having failed to detect signi®cant changes (Catron et al 1986;Dujic et al 1993; Thorsen et al 1995). In the ®rst hours after open-sea bounce dives however, signi®cant decreases of expiratory volumes and¯ows were obtained and factors related to immersion and increased breathing resistance were considered to have contributed to these respiratory changes (Skogstad et al 1996) A recent study on subjects signi®cant changes in post-dive lung function after 3 and 24 h (Tetzla et al 1999), indicating that exposure to immersion and depth alone may not necessarily cause signi®cant subacute respiratory eects.…”
Section: Introductionmentioning
confidence: 99%
“…10 for a review]. Static lung volumes were found to increase whereas dynamic lung volumes decrease after diving [11,12]. Moreover, breathing cold and dry air from a self-contained underwater breathing apparatus may worsen respiratory function [13].…”
Section: Introductionmentioning
confidence: 99%